2020
DOI: 10.1007/s10926-020-09937-4
|View full text |Cite
|
Sign up to set email alerts
|

Gig Workers with Disabilities: Opportunities, Challenges, and Regulatory Response

Abstract: Purpose This article examines gig work—typified by technologically-based, on-demand, independent contractor arrangements—for people with disabilities. Methods To do so, it draws upon prior and current research to describe the nature of gig work for people with disabilities, as well as the challenges and new prospects that such work presents. It also discusses recent regulatory reforms and proposes improvements, particularly in light of the current pandemic. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Nonetheless, effective workplace accommodations are not always available to all workers [11]. While people with health conditions, impairments, and other disabilities are more likely to request workplace accommodations than those without disabilities [12], there likely are disparities in who actually receives them.…”
Section: Supreme Court Case Tennessee V Lane [1]mentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, effective workplace accommodations are not always available to all workers [11]. While people with health conditions, impairments, and other disabilities are more likely to request workplace accommodations than those without disabilities [12], there likely are disparities in who actually receives them.…”
Section: Supreme Court Case Tennessee V Lane [1]mentioning
confidence: 99%
“…One survey of over three hundred Chief Financial Officers has found that almost three-quarters (74%) of private companies in the U.S. may transition at least five percent of their on-site employees to permanently remote positions [17]. These remote work arrangements may benefit people with disabilities (or those who have family members with disabilities): better outcomes may result from work-related accommodations in their own homes [11,18,19,85]. And the pandemic raises the question of whether many of the changes made will remain the "new norm" once the pandemic ends, further benefitting people with disabilities and their families.…”
Section: Supreme Court Case Tennessee V Lane [1]mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent JOOR article [1], authors Harpur and Blanck examined gig work for people with disabilities, and we write with an important update triggered by this month's election and related developments.…”
mentioning
confidence: 99%